Lucky Luke. 12, The rivals of Painful Gulch - Goscinny, 1926-1977.; Morris, 1923-; Spear, Luke (Canterbury, Kent [England] : Cinebook, 2008)
The O'Timmins and the O'Haras, two rival families that have been been fighting in Painful Gulch for decades, continue their conflict even after Lucky Luke is appointed mayor to find a peaceful resolution.
First published: Paris: Dargaud Editeur, c1971, under title: Lucky Luke: Les rivaux de Painful Gulch.
Spine title.
Translated from the French.
3.0
3-6.
3-6
Keywords: Cowboys -- Comic books, strips, etc -- Juvenile fiction; Lucky Luke (Fictitious character) -- Comic books, strips, etc -- Juvenile fiction; Vendetta -- Comic books, strips, etc -- Juvenile fiction; Cartoons and comics; Cowboys -- Fiction; Lucky Luke (Fictitious character) -- Fiction; Vendetta -- Fiction; Comic books, strips, etc; Cowhands -- Comic books, strips, etc -- Fiction; Graphic novels; Lucky Luke (Fictional character) -- Comic books, strips, etc -- Fiction; Vendetta -- Comic books, strips, etc -- Fiction; Western comic books, strips, etc; West (U.S.) -- Fiction; Graphic novels; Western comic books, strips, etc